Association of Medicaid Expansion With Neuraxial Labor Analgesia Use in the United States: A Retrospective Cross-Sectional Analysis. (18th February 2022) - Xiao, Maggie Z. X.; Whitney, Dylan; Guo, Nan; Sun, Eric C.; Wong, Cynthia A.; Bentley, Jason; Butwick, Alexander J.
Abstract : BACKGROUND: The Affordable Care Act has been associated with increased Medicaid coverage for childbirth among low-income US women. We hypothesized that Medicaid expansion was associated with increased use of labor neuraxial analgesia. METHODS: We performed a cross-sectional analysis of US women with singleton live births who underwent vaginal delivery or intrapartum cesarean delivery between 2009 and 2017. Data were sourced from births in 26 US states that used the 2003 Revised US Birth Certificate. Difference-in-difference linear probability models were used to compare changes in the prevalence of neuraxial labor analgesia in 15 expansion and 11 nonexpansion states before and after Medicaid expansion. Models were adjusted for potential maternal and obstetric confounders with standard errors clustered at the state level. RESULTS: The study sample included 5, 703, 371 births from 15 expansion states and 5, 582, 689 births from 11 nonexpansion states. In the preexpansion period, the overall rate of neuraxial analgesia in expansion and nonexpansion states was 73.2% vs 76.3%. Compared with the preexpansion period, the rate of neuraxial analgesia increased in the postexpansion period by 1.7% in expansion states (95% CI, 1.6–1.8) and 0.9% (95% CI, 0.9–1.0) in nonexpansion states. The adjusted difference-in-difference estimate comparing expansion and nonexpansion states was 0.47% points (95% CI, −0.63 to 1.57; P = .39). CONCLUSIONS: Medicaid expansion was not associated with an increase in the rate of neuraxial labor analgesia in expansion states compared to the change in nonexpansion states over the same time period. Increasing Medicaid eligibility alone may be insufficient to increase the rate of neuraxial labor analgesia.